2022
DOI: 10.1021/acsomega.1c07393
|View full text |Cite
|
Sign up to set email alerts
|

Gold Tablets: Gold Nanoparticles Encapsulated into Dextran Tablets and Their pH-Responsive Behavior as an Easy-to-Use Platform for Multipurpose Applications

Abstract: Many applications using gold nanoparticles (AuNPs) require (i) their functionalization with a biopolymer to increase their stability and (ii) their transformation into an easy-to-handle material, which provide them with specific properties. In this research, a portable tablet platform is presented based on dextran-encapsulated gold nanoparticles (AuNPs-dTab) by a ligand exchange reaction between citrate-capped gold nanoparticles (AuNPs-Cit) and dextran. These newly fabricated tablets were characterized utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…AuNPs within dextran matrices. 76 This design ensures resilience to alkaline conditions while exhibiting heightened responsiveness in acidic environments due to nanogold aggregation within the lower pH range. Along the same lines, AuNPs encapsulated with a pullulan matrix tablet have been generated.…”
Section: Nanoparticle-based Tablets a Tablet Incorporating Gold Nanop...mentioning
confidence: 99%
See 1 more Smart Citation
“…AuNPs within dextran matrices. 76 This design ensures resilience to alkaline conditions while exhibiting heightened responsiveness in acidic environments due to nanogold aggregation within the lower pH range. Along the same lines, AuNPs encapsulated with a pullulan matrix tablet have been generated.…”
Section: Nanoparticle-based Tablets a Tablet Incorporating Gold Nanop...mentioning
confidence: 99%
“…The peroxidase catalytic activity of these AuNPspullulan tables is showcased through the oxidation of the substrate. 76 These AuNPs-based tablets provide sensor activity in measuring the levels of glucose and hydrogen peroxide.…”
Section: Nanoparticle-based Tablets a Tablet Incorporating Gold Nanop...mentioning
confidence: 99%
“…Au NPs can provoke reactive oxygen species (ROS) production in A549 cells and oxidative stress-mediated apoptosis to exert anticancer activity in lung cancer . However, many applications using Au NPs require a combination with different ligands to increase their stability and provide them with specific properties . Recent research has found dextran as a stabilizing and reducing agent for the synthesis of Au NPs .…”
Section: Introductionmentioning
confidence: 99%
“…12 However, many applications using Au NPs require a combination with different ligands to increase their stability and provide them with specific properties. 13 Recent research has found dextran as a stabilizing and reducing agent for the synthesis of Au NPs. 14 Dextran is defined as a polysaccharide consisting of glucose units.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 In recent studies, the incorporation of reagent encapsulation techniques has been preferred to ensure swift detection in a liquid phase by discharging enclosed reagents during the testing process. 18–21 This combined method not only yields a sensitive detection system but also merges the beneficial aspects of point-of-care analytical devices. Therefore, scientists and researchers are keen to investigate novel platforms for point-of-care devices.…”
Section: Introductionmentioning
confidence: 99%